Case Report: Surgical repair of mitral prolapse caused by papillary muscle elongation using premeasured artificial chordae: a case series - Gan, Lixi; Chen, Oudi; Chen, Fanyu; Wang, Weiteng; Qing, Hongkun; Jian, Xuhua (Frontiers in Cardiovascular Medicine, 2025)
Artificial chordae are increasingly used to repair mitral prolapse. The application of premeasured artificial chordae facilitates the creation of chordae with an appropriate length. Herein, we describe our experience of applying premeasured artificial chordae in 14 cases of mitral prolapse caused by elongated papillary muscles, with an emphasis on the importance of restoring the physiological features of sub-valvular structures during mitral valve repair.